2017
DOI: 10.3389/fmicb.2017.01991
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Lipoteichoic Acid Synthesis Causes a Failure in Executing the Colony Developmental Program in Bacillus subtilis

Abstract: Colonies are an abundant form of bacterial multicellularity; however, relatively little is known about the initial stages of their construction. We have previously described that colony development of the soil bacterium Bacillus subtilis is a highly ordered process, typically initiating with the formation of extending cell chains arranged in a Y shape structure. Furthermore, we demonstrated that Y arm extension is a key for defining the size of the future colony. Here we conducted a genetic screen surveying fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…However, the preservation of Glc‐TA in nature emphasizes the necessity of these surface molecules for bacterial physiology. TAs have been implicated in various cellular processes, such as structuring cell shape, cell division, colony formation and ion homeostasis (Weidenmaier and Peschel, ; Brown et al , ; Schneewind and Missiakas, ; Mamou et al , ), yet the role of glycosylation of TAs is much less understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, the preservation of Glc‐TA in nature emphasizes the necessity of these surface molecules for bacterial physiology. TAs have been implicated in various cellular processes, such as structuring cell shape, cell division, colony formation and ion homeostasis (Weidenmaier and Peschel, ; Brown et al , ; Schneewind and Missiakas, ; Mamou et al , ), yet the role of glycosylation of TAs is much less understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the soil bacterium B. subtilis , the absence of LTA affects divalent cation homeostasis and leads to increased sensitivity to diverse antibiotics and lysozyme, and the absence of WTA leads to drastic morphological alterations ( 9 ). It has also been shown that the deficiency in LTA synthesis leads to smaller colony sizes due to a failure in the execution of the colony developmental program in B. subtilis ( 10 ). Additionally, B. subtilis cells lacking both WTA and LTA are not viable, reflecting the importance of these cell polymers ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Light microscopy inspection of these mutants revealed elongated cells twice as long as the wild type cells, and exhibiting bending and curving (Selle et al, 2017;Selle et al, 2014). However, contrarily to L. plantarum, and ltaS mutants of other species (Mamou et al, 2017;Oku et al, 2009;Schirner et al, 2009), no relevant growth defect was observed in L. acidophilus NCFM upon ltaS mutation (Mohamadzadeh et al, 2011). Both L.…”
Section: Discussionmentioning
confidence: 94%